Discovery of Bioactive Metabolites in Biofuel Microalgae That Offer Protection against Predatory Bacteria - Bagwell, Christopher E.; Abernathy, Amanda; Barnwell, Remy; Milliken, Charles E.; Noble, Peter A.; Dale, Taraka; Beauchesne, Kevin R.; Moeller, Peter D. R. (Frontiers in Microbiology, 2016)
Microalgae could become an important resource for addressing increasing global demand for food, energy, and commodities while helping to reduce atmospheric greenhouse gasses. Even though Chlorophytes are generally regarded safe for human consumption, there is still much we do not understand about the metabolic and biochemical potential of microscopic algae. The aim of this study was to evaluate biofuel candidate strains of Chlorella and Scenedesmus for the potential to produce bioactive metabolites when grown under nutrient depletion regimes intended to stimulate production of triacylglycerides. Strain specific combinations of macro- and micro-nutrient restricted growth media did stimulate neutral lipid accumulation by microalgal cultures. However, cultures that were restricted for iron consistently and reliably tested positive for cytotoxicity by in vivo bioassays. The addition of iron back to these cultures resulted in the disappearance of the bioactive components by LC/MS fingerprinting and loss of cytotoxicity by in vivo bioassay. Incomplete NMR characterization of the most abundant cytotoxic fractions suggested that small molecular weight peptides and glycosides could be responsible for Chlorella cytotoxicity. Experiments were conducted to determine if the bioactive metabolites induced by Fe-limitation in Chlorella sp. cultures would elicit protection against Vampirovibrio chlorellavorus, an obligate predator of Chlorella. Introduction of V. chlorellavorus resulted in a 72% decrease in algal biomass in the experimental controls after 7 days. Conversely, only slight losses of algal biomass were measured for the iron limited Chlorella cultures (0–9%). This study demonstrates a causal linkage between iron bioavailability and bioactive metabolite production in strains of Chlorella and Scenedesmus. Further study of this phenomenon could contribute to the development of new strategies to extend algal production cycles in open, outdoor systems while ensuring the protection of biomass from predatory losses.